2022
DOI: 10.5093/anyes2022a19
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Attitudes and Long-Term Posttraumatic Growth in Victims of Terrorist Attacks

Abstract: Background: The theoretical models of posttraumatic growth (PTG) assume that a change in core beliefs or attitudes about the world and oneself is at the root of PTG. However, there are few studies on the relationship between these attitudes and PTG and their results are contradictory. The contradictions could be clarified using an instrument that assesses attitudes more specifically related to the traumatic event (traumatic dysfunctional attitudes) and analyzing whether said relationship is linear or an invert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 26 publications
3
4
0
Order By: Relevance
“…That is, people who had suffered a traumatic event and who afterwards felt closer to others or believed they could rely on others in a crisis, or those who felt stronger and more self-confident, were also likely to believe that the emotional distress caused by the traumatic experience would be moderately chronic and that the psychological damage they had suffered would be moderately irreversible. This finding echoes the results of a study by Liébana et al (2022), which found that the likelihood of victims of terrorist attacks to express new appreciation for life had an inverted U-shaped relationship with the overall level of dysfunctional trauma-related attitudes and, especially, with the level of dysfunctional attitudes expecting distress to be chronic. Therefore, both the results of the present study and those of Liébana et al (2022) lend support to the arguments of Janoff-Bulman ( 2004), who maintained that, over time, the basic positive attitudes and beliefs of many of those who have had traumatic experiences are rebuilt, but that at the same time these people also adopt negative or dysfunctional beliefs.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…That is, people who had suffered a traumatic event and who afterwards felt closer to others or believed they could rely on others in a crisis, or those who felt stronger and more self-confident, were also likely to believe that the emotional distress caused by the traumatic experience would be moderately chronic and that the psychological damage they had suffered would be moderately irreversible. This finding echoes the results of a study by Liébana et al (2022), which found that the likelihood of victims of terrorist attacks to express new appreciation for life had an inverted U-shaped relationship with the overall level of dysfunctional trauma-related attitudes and, especially, with the level of dysfunctional attitudes expecting distress to be chronic. Therefore, both the results of the present study and those of Liébana et al (2022) lend support to the arguments of Janoff-Bulman ( 2004), who maintained that, over time, the basic positive attitudes and beliefs of many of those who have had traumatic experiences are rebuilt, but that at the same time these people also adopt negative or dysfunctional beliefs.…”
Section: Discussionsupporting
confidence: 84%
“…These more positive constructs are all either directly or indirectly involved in Tedeschi and Calhoun's (1995;Tedeschi et al, 2018) model of PTG. In fact, instruments assessing these positive constructs tend to include inverse items that reflect their negative or dysfunctional variants, and vice-versa (Liébana et al, 2022). This argument supports this study's focus on the negative or dysfunctional variants of metacognitive beliefs, self-focused attention and trauma-related attitudes, but the choice of this focus also arose from the desire to investigate whether the association between these variables and PTG might be curvilinear rather than linear.…”
Section: R E S U M E Nsupporting
confidence: 57%
See 3 more Smart Citations